Answer:
see explanation
Explanation:
multiplying the matrices on the left side
=
![\left[\begin{array}{ccc}6\\-9\\\end{array}\right]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tszx3oqzwo8woboyn6ycdrpmsz2c2tjr71.png)
Equating corresponding components on both sides gives
3x + 4y = 6 → (1)
6x + y = - 9 → (2)
multiply (2) by - 4
- 24x - 4y = 36 → (3)
Add (1) and (3) term by term
- 21x = 42 ( divide both sides by - 21
x = - 2
substitute x = - 2 into either (1) or (2)
(1) : - 6 + 4y = 6 ( add 6 to both sides )
4y = 12 ( divide both sides by 4 )
y = 3
solution is (- 2, 3 )